Computed tomogram guided fine-needle aspiration cytology of lung mass with histological correlation: A study in Eastern India - Mondal, Santosh Kumar; Nag, Dipanwita; Parikh, Biren; Shah, Manoj; Davara, Kajal (South Asian Journal of Cancer, 2013)
Background: Fine-needle aspiration cytology (FNAC) is an important and useful investigation, and is considered next to imaging in the rapid diagnosis of pulmonary mass lesion for the last few decades. Aims: To assess the role of Computed Tomogram (CT) guided FNAC in pulmonary mass lesions; to analyze the results; and to compare with histopathological findings. Materials and Methods: The clinical, radiological, and cytological data of 130 patients were prospectively studied who underwent CT guided FNAC from October 2009 through September 2011. Thereafter these patients underwent bronchoscopic/trucut biopsy/ lobectomy, whatever clinically indicated. Smears and tissue sections were evaluated simultaneously to reach at a definite diagnosis. Results: Out of 130 cases, we found adequate FNAC smear and histopathology reports only in 124 cases. The age range varied from 35 to 73 years with the peak in the fifth to sixth decades. The benign lesions were 10 (8.07%) and malignant lesions were114 (91.93%) shown by cytology. The most common tumor was adenocarcinoma (51.72%) followed by squamous cell carcinoma (22.41%) and small cell carcinoma 6.89%. Diagnostic accuracy of CT guided FNAC was 95%. Post procedural complications such as hemorrhage and chest pain were minimal and were noted only in three cases. Conclusion: CT guided FNAC of pulmonary masses provides simple, easy, and reliable method for reaching rapid tissue diagnosis with minimal complication.
Keywords: FNAC; histological correlation; pulmonary mass